Pendidikan Agama Islam Berwawasan Inklusif-Pluralis - Nasri Kurnialoh (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: In countries with multi-ethnic consists of religion, and race such as Indonesia, the role of Islamic religious education is very important and strategic. See sectarian conflict based on culture, ethnicity, race and religion going on in our society, it seems the paradigm of inclusive vision of Islamic education which emphasizes the concept of pluralism in sosial life need to be developed. Furthermore, Islam is an inclusive religious education should provide a comprehensive understanding of religion through teaching with respect religious differences without losing identity as followers of a particular religion. Keywords : Islamic Education, Inclusive, Pluralist.